THE MAIN MARKERS OF AUTOIMMUNE RHEUMATIC DISEASES AND THEIR INTERPRETATION - A. S. Burlakova; V. V. Vasilenko; D. L. Vinogradov (Архивъ внутренней медицины, 2016)
The aim of this work is to systematize of the data on markers of autoimmune rheumatic diseases. The article includes basic information taking the latest recommendations of 2014 into account. All pieces of material are presented  in the form of tables for convenient use in daily practice of any specialist.